1989
DOI: 10.1111/j.1440-1630.1989.tb01208.x
|View full text |Cite
|
Sign up to set email alerts
|

Professional Literature: One View of a National Perspective

Abstract: Content, citation and theme analyses of articles and editorials published during two five year periods (1963‐67 and 1983‐87) in the Australian Occupational Therapy Journal are presented. A comparison of the two publication periods shows that: there has been no increase in the number of journal issues per year, nor in the total number of articles published since 1963. The number of articles in the research category has substantially increased; research appears to reflect the scope of practice. However, the need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…Madill et al . () and Potter () have reported similar trends in which the number of Australian occupational therapist authored research articles has expanded. This increase is likely related to the number of occupational therapy‐specific journals that have recently been accepted into JCR (e.g.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Madill et al . () and Potter () have reported similar trends in which the number of Australian occupational therapist authored research articles has expanded. This increase is likely related to the number of occupational therapy‐specific journals that have recently been accepted into JCR (e.g.…”
Section: Discussionmentioning
confidence: 71%
“…Several content reviews of AOTJ articles have been published previously (e.g. Bell & Anderson, ; Cusick, ; Madill, Brintnell & Stewin, ; Ziviani, Behan & Rodger, ). Ziviani et al .…”
Section: Introductionmentioning
confidence: 99%
“…(Gutman, 2008a). Other studies of the occupational therapy literature have also found that pediatrics is a focus of journal publications (Brown, Rodger, & Brown, 2005;Case-Smith, 2007;Madill et al, 1989;Mountain, 1997;Ziviani, Behan, & Rodger, 1984).…”
Section: Resultsmentioning
confidence: 99%
“…Professional journals are a primary source of information about a profession's undertakings (34) and can serve as an indicator for the state of the art within the subject. Professional journals show the strengths and maturity of the subject through debating and challenging presented ideas.…”
Section: Professional Publications' Significance For Elderly Researchmentioning
confidence: 99%